Fenología de orquídeas nativas rescatadas de desmontes autorizados en la provincia de Misiones - Haussecker, Ricardo Daniel; Bischoff, Doris Irene (Facultad de Ciencias Forestales, UNaM. EEA Montecarlo , INTA. Colegio de Ingenieros Forestales de Misiones (Coiform.), 2023)
In Argentina, near 300 species of orchids exist; 147 of them can be found in Misiones, some of them are near extinction. The work objective was to preserve 45 of them, evaluating their adaption to breeding under green houses. 4 years’ phonologic observations have been conducted. The epiphytes orchids adapted very well on wooden supports and the earth ones, adapted well in plant pts filed with forest mantel. Zygopetalum maxillare, Isabelia virginalis and Maxillaria spegazziniana did not do well. Flowering was registered in 40 species all year round.